Hypercoagulable States Therapy in Nonarteritic Anterior Ischemic Optic Neuropathy (NAION) (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2021)
Background Ischemic optic neuropathy is one of the main causes of blindness or visual impairment in middle age or elderly population. Nonarteritic Anterior Ischemic Optic Neuropathy (NAION) is the most common type of ischemic optic neuropathy. Systemic risk factors such as hypertension, diabetes mellitus, nocturnal hypotension, sleep apnea, cardiovascular disease and hypercoagulable states are related to NAION. The aim of the study was to evaluate the clinical outcome of hypercoagulable states therapy in NAION patients. Methods This study is a retrospective study conducted at Cipto Mangunkusumo Hospital Jakarta. All NAION patients with age more than 19 y.o were included. Patients were divided into 4 group; group 1: NAION patients treated with hypercoagulable states therapy, group 2: NAION patients treated with anticoagulant therapy, group 3: NAION patients treated with antiplatelet therapy and group 4: NAION patient without anticoagulant, antiplatelet or hypercoagulable states therapy. Results The total sample were 49 patients (49 eyes). Twenty-six patients (56.5%) were diagnosed with hypercoagulable state. In group 1 ? 3 half of the patients (50%) had clinical improvements with anticoagulant, antiplatelet and hypercoagulable therapy. Conclusion Hypercoagulable states therapy may improve clinical outcome of NAION..